A discourse analysis of English travel advertisements - Bùi Thị Huy Huyền (2007)
Interpersonal metaphor is a new concept of metaphors working in language in general. Yet, there have not been many researches on this area. On the theoretical framework of interpersonal metaphor by Halliday in his book An …